Ambidextrous innovation in project management: a systematic literature review - Al Saied, Mohammad; McLaughlin, Patrick (MDPI, 2024)
Projects work under constant pressure of resource and time constraints. In order to perform effectively and efficiently, innovation seems to be a significant factor. However, due to the different nature of projects as compared to the organization, projects have been finding it difficult to undertake such innovation. However, ambidextrous innovation, which seeks to balance exploratory and exploitative innovation, offers a possible solution. However, research on the relationship between ambidextrous innovation and project management is at an early stage. The purpose of the present research is to undertake a systematic review of the literature to build and synthesize the understanding of innovation ambidexterity at the project level. Following the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) guidelines, our research collected data from the Web of Science and SCOPUS databases. By adhering to the PRISMA approach, we ensured a rigorous and transparent approach to the systematic review study, allowing for comprehensive data collection and analysis. The results of the present review study suggest that interest is building rapidly to incorporate ambidextrous innovation into project management. Ambidextrous innovation seemed to positively impact both the performance and capability of projects to undertake the innovation. Further, important drivers such as organizational culture, knowledge management, innovation activities, and agility play key roles in undertaking ambidextrous innovation at the project level. Further, elements of the team such as team integration, alignment, and knowledge utilization also play key roles. Finally, the avenue of future research has also been highlighted.
Keywords: ambidextrous innovation; project management; explorative innovation; exploitative innovation